2018
DOI: 10.1007/s10557-018-6800-3
|View full text |Cite
|
Sign up to set email alerts
|

Statin Utilization Patterns and Outcomes for Patients with Acute Coronary Syndrome During and Following Inpatient Admissions

Abstract: PurposeHigh-intensity statins (HIS) are recommended by current treatment guidelines for patients with clinical atherosclerotic cardiovascular disease and should be administered soon after an acute coronary syndrome (ACS) event and maintained thereafter. However, adherence to guidelines remains adequate. Statin utilization patterns during index hospitalization and the first year after ACS event, and the association between statin utilization and post-discharge clinical and economic outcomes, are described.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…This percentage increased to 13.2% during hospitalization and to 16.4% in the follow-up year. Most patients received low to moderate intensity statin doses (up to 45% in a year) 12) . Colantonio et al , retrospectively analyzed approximately 58,000 Medicare patients six months and two years after their hospitalization for MI, and found that the percentage of patients using HIS with high adherence dropped from 59% to 41.6%.…”
Section: Adherence To Statin Treatment Ldl-c Goals Achievement and Cmentioning
confidence: 99%
“…This percentage increased to 13.2% during hospitalization and to 16.4% in the follow-up year. Most patients received low to moderate intensity statin doses (up to 45% in a year) 12) . Colantonio et al , retrospectively analyzed approximately 58,000 Medicare patients six months and two years after their hospitalization for MI, and found that the percentage of patients using HIS with high adherence dropped from 59% to 41.6%.…”
Section: Adherence To Statin Treatment Ldl-c Goals Achievement and Cmentioning
confidence: 99%
“…Compared with other studies, we observed a low percentage of Emirati patients who received LLT (58.1%) while being at high risk of CV events. [ 22 23 24 ] Thus, it confirms that the use of statins in the UAE remains comparatively low despite the guideline recommendation worldwide. Further analysis showed that suboptimal dosing of statin prescription in secondary prevention and poor intensification of statin therapy were only moderate after ACS.…”
Section: Discussionmentioning
confidence: 55%
“…Yet, in some regions there is suboptimal use of lipid-lowering therapy at time of discharge from ACS. For example, national registry data from the USA found 39.3% of patients were not prescribed any lipid-lowering therapy during a hospital admission for ACS, although this reduced to 22.3% by 1-year follow-up 4. This is different to registry data in New Zealand and Australia where 95%8 and 92.7%7 of patients, respectively, post-ACS were prescribed statins on discharge.…”
mentioning
confidence: 83%
“…Among those with established atherosclerotic cardiovascular disease (ASCVD), poor statin adherence has been reported to be 47.2% in real-world registry data 2. Discontinuation rates have been reported ranging from 14%3 to 26.5%4 at 12 months in both large multicentre randomised clinical trial (RCT) data and national registries, with long-term discontinuation being 51% after 7 years in a large-scale RCT involving 39 countries 3. In a systematic review including 28 studies (5 nested case–control and 22 cohort studies), adherence to statin use in patients at high risk of ASCVD and those with established ASCVD was associated with a reduction in subsequent cardiovascular events (OR 1.22–5.26) and improved survival (OR 1.79–5.00) 5.…”
mentioning
confidence: 99%